An Urartian rock inscription on Mt Taragheh, in Iranian Azerbaijan - Salvini, Mirjo; Dara, Maryam (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
A new Urartian rock inscription has been found on Mt Taragheh, near the village of Elmabad, west of Bukân in Iranian Azerbaidjan. The available documentation is very poor, but the authors tried to decipher an old film in order to reconstruct fragments of a cuneiform text going back to the beginning of Urartian history. The names of King Išpuini and his son Minua suggest a dating towards the last quarter of the 9th century BC. It is the most ancient Urartian text found in the Western Azerbaijan province of Iran.